Respuesta :

Hello,

[tex]\boxed{P(X = k) =( {}^{n} _{k}) \times p {}^{k} \times (1 - p) {}^{n - k} }[/tex]

[tex]P(X= k) = ( {}^{12} _{6}) \times 0.51 {}^{6} \times (1 - 0.51) {}^{12 - 6} [/tex]

We have :

[tex]( {}^{n} _{k}) = \frac{n!}{k!(n - k)!} [/tex]

[tex]( {}^{12} _{6}) = \frac{12!}{6!(12 - 6)!} = \frac{12!}{6!6!} = \frac{12 \times 11 \times 10 \times ... \times 1}{2(6 \times 5 \times 4 \times... \times 1) } = \frac{12 \times 11 \times 10 \times 9 \times 8 \times 7 }{6 \times 5 \times 4 \times 3 \times 2 \times 1} = 924[/tex]

[tex]P(X = k) = 924 \times 0.51 {}^{6} \times 0.49 {}^{6} = 0.2250[/tex]

ACCESS MORE